Prevalence of Frailty and Its Associated Factors among Post-Tuberculosis Patients Following Completion of Anti-Tubercular Therapy: A Hospital-Based Cross-Sectional Study in Tamil Nadu, India (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Tuberculosis (TB) remains a major public health challenge despite effective anti-tubercular therapy (ATT). Many patients continue to experience physical, nutritional, functional, and psychosocial impairments after treatment, increasing their risk of frailty. However, evidence on frailty among post-tuberculosis patients in India is limited. Objective: To determine the prevalence of frailty and identify its associated demographic, clinical, nutritional, and psychosocial factors among post-tuberculosis patients after completion of ATT. Methods: A hospital-based cross-sectional study was conducted among 150 post-tuberculosis patients attending the Department of Pulmonary Medicine at a tertiary care hospital in Erode. Frailty was assessed using the FRAIL Scale, fatigue using the Fatigue Severity Scale, nutritional status using the Mini Nutritional Assessment–Short Form and body mass index, and social support using the Multidimensional Scale of Perceived Social Support. Statistical significance was set at p < 0.05. Results: Frailty was identified in 20.7% of participants, while 41.3% were pre-frail. Frailty was significantly associated with older age, underweight status, malnutrition, higher fatigue severity, and lower perceived social support. Advanced age, malnutrition, underweight status, severe fatigue, and low social support were independent predictors of frailty. Conclusion: Frailty is common among post-tuberculosis patients and is associated with several modifiable factors. Routine frailty screening, and multidisciplinary rehabilitation may improve long-term recovery and quality of life.
Keywords: Tuberculosis (TB); FRAIL Scale; anti-tubercular therapy (ATT)